Translating religion in the dream of the red chamber - Barry Lee Reynolds; Chao, Chih Liao (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The world seems aware that China is among the countries with the largest Buddhist population. The global village may say that in Taiwan and Mainland China, Buddhism, Confucianism and Taoism are combined, mixed and blurred. Dream of the Red Chamber (紅樓夢Hóng Lóu Mèng) was written in the 18th century against such a backdrop. Since the 1990s, English as a Foreign Language teaching and learning, especially in Taiwan, has aimed at mastering five skills—translation added to traditionally recognized skills of listening, speaking, reading and writing. Taiwanese students may feel translating from English to Chinese easier due to their firm grasp of the target language and culture; however, students should be aware that translating from Chinese to English aids not only in disseminating source language cultural knowledge but also is more profitable than translating from English to Chinese in terms of wages earned. When rendering Chinese literary works to English, a translator inevitably encounters the problem of cultural translation. This paper concentrates on translation of texts, including Taoism and Buddhism expressions in Hóng Lóu Mèng by Cáo Xuěqín, into English by David Hawkes and Xianyi Yang & Gladys Yang. Translating Hóng Lóu Mèng in the 1970s, both renditions made use of endnotes, transliteration, as well as a number of other methods. Examples will explain how they did the tedious job. While translating Hóng Lóu Mèng to English, both made the religious background a little confusing to target language readers. Xianyi Yang & Gladys Yang’s version was found to be more faithful to the religion but at the cost of readability. Implications for teaching translation of texts with religious contexts are discussed.